London uncanny: a gothic guide to the capital in weird history and fiction - Bloom, Clive (Bloomsbury Academic, 2025)
London is both a physical metropolis and a psychic encounter. Depraved depictions of the city in fiction, film, poetry, television and theatre have merged with its dark history, creating a phantasmagoria of murder, vice and the unnatural. In this panoptic look at England's capital at its most eerie and macabre, Clive Bloom takes a tour of Gothic London's uncanny literature, arcane events and its infamous geographies. With inhabitants from Jack the Ripper and Aleister Crowley to Sweeney Todd and Count Dracula, Dark City presents London as haunted by its past and haunting the present